African Healthcare Business and Investment Opportunities - Babatunde Omilola,; N’doh A. Sanogo, (Public Health, 2024)
As the cost of medical care continues to increase in many developed countries (e.g., United States), as well as in some developing nations, with no or little improvement in population level health indicators (e.g., infant mortality), the limits to curative, clinical medicine becomes apparent.